Klausul Akad Musyarakah Mutanaqishah KPR Bedasarkan Ketetapan Fatwa DSN MUI - Rusli, Dodi Yarli; Ma'wa, Nada Roudotul (Jurnal Hukum Ekonomi Syariah, 2018)
The purpose of the authors to conduct this research is to determine the extent of the application of the MUI Fatwa DSN No. 73 / DSN-MUI / XI / 2008 perfected by DSN MUI Fatwa No. 01 / DS-MUI / X / 2013 by BNI Syariah Bekasi Branch Office. The method used is qualitative with a descriptive approach, namely by clearly describing everything that is obtained in the field. Techniques in collecting data in this study were obtained through interviews, and literature study. The results of this study indicate that the BNI Syariah Bekasi Branch Office is worth mentioning that the Sharia Bank applies sharia principles in accordance with applicable regulations, namely Fatwa DSN MUI No. 01 / DSMUI / X / 2013, it's just that there are a number of things that BNI Syariah needs to pay attention to in its implementation of applicable financing products, especially Syariah KPR Griya KPR financing.